Rapid Progression of Cataract in Patient with Newly Diagnosed Diabetes Mellitus Type 2 - Grąbczewski, Andrzej; Samelska, Katarzyna; Kurowska, Anna; Skopiński, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
The purpose of the article is to present a rapid-course of cataract progression that developed after glycemia normalization in a patient with newly-diagnosed type 2 diabetes mellitus and reviewing the pathomechanism of the diabetic cataract and the cataract swelling.